Aphid (Hemiptera: Aphididae) Diversity in Potato Production Areas in Tucumán, Argentina - Avila, Ana Lucía; Vera, M. Alejandro; Ortego, Jaime; Willink, Eduardo; Ploper, Leonardo Daniel; Conci, Vilma Cecilia (2018)
Aphids are recognized as important plant pests worldwide and they are major vectors of viruses. It is necessary to identify the aphid species in an agroecosystem in order to develop appropriate pest management strategies. The aim of this work was to determine the taxonomic diversity of aphid species present in potato crops in different agroecological regions of Tucumán, Argentina. Monitoring was done by 2 methods: modified Moericke yellow water traps were used for the alatae, while the apterae were collected directly from the plants. A total of 15,169 winged aphids were caught and 7,455 apterae colonizing the crop were collected. Fifty-six species were identified, 27 of which were present in all regions surveyed. Differences in species diversity between regions are discussed.